Deliberation in contexts of conflict: An introduction (2014)
Is there any fundamental difference between ideal forms of deliberative democracy in deeply divided societies and those relatively stable societies where this idea first took root? Deliberative practices are supposed to invigorate contemporary political systems hindered by problems such as citizen apathy and legitimacy challenges. But the deliberative recipe is still in need of further specification in order to make it a feasible and tangible option in the case of stable democracies. And if we rather speak of a context of a profound societal division in terms of ideology, class, ethnicity, language or religion, then grounding efforts might seem even more daunting.